2019
DOI: 10.7759/cureus.6144
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Infiltration of Mitral Valve: A Rare Case Report and Review of Literature

Abstract: Adipose tissue is a normal anatomical finding in the heart but fat infiltration in cardiac valves is extremely rare with very few cases reported in the literature. We report a case of fatty infiltration in a mitral valve replaced for mitral valve prolapse causing severe mitral regurgitation in a 65-year-old male who presented with shortness of breath and upper respiratory tract infection. The histopathological examination of the mitral valve revealed sheets of mature adipocytes in the spongiosa layer leading t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…The enrichment of PPAR signaling, the uniform increased methylation of the subnetwork's constituent genes in mitral compared to aortic valves and APOA5 being a hub node, indicate that this subnetwork exhibits major methylation alterations related to the metabolism of lipids. The regulation and expression of lipid-related genes need to be further dissected as it has been reported in a previous study that increased fatty infiltration of valves is observed in MVP ( 89 ).…”
Section: Discussionmentioning
confidence: 99%
“…The enrichment of PPAR signaling, the uniform increased methylation of the subnetwork's constituent genes in mitral compared to aortic valves and APOA5 being a hub node, indicate that this subnetwork exhibits major methylation alterations related to the metabolism of lipids. The regulation and expression of lipid-related genes need to be further dissected as it has been reported in a previous study that increased fatty infiltration of valves is observed in MVP ( 89 ).…”
Section: Discussionmentioning
confidence: 99%